PENGADAAN TANAH UNTUK KEPENTINGAN UMUM IMPLIKASINYA DENGAN ALIH FUNGSI LAHAN DAN PENATAAN RUANG - Lisdiyono, Edy (MEDIA HUKUM, 2014)
The procurement of land for the public interest in fact is not able to avoid in executing the development because of the people increasing and the industrial growth. The land replacement from the agriculture lands are used to the interest non-agriculture lands, such as industrial areas, or for residences/housing every year has become increased.